Influence of glucose on Candida parapsilosis virulence factors - Pereira, Leonel João Pais (2013)
Candida parapsilosis is a pathogenic fungus responsible for a high number of oral candidosis, predominantly due to the growth in a biofilm form on indwelling medical devices. One of the major contributions for C. parapsiloisis virulence is its versatility to adapt to a variety of different environmental factors. The development of Candida biofilms has important clinical repercussions because of their resistance to antifungal therapy and the protection against host immune defences. Candida biofilms are characterized by easily glucose adaptation. However, it remains unclear how glucose affect C. parapsilosis biofilms formation and virulence. Thus, this work aimed to study the influence of glucose in biofilm formation ability and matrix composition of C. parapsilosis and in the expression of virulence genes such as BCR1, FKS1 and OLE1. For that a full characterisation of in vitro biofilm formation with different concentrations of glucose (0.2, 2 and 10 %) was examined. Biofilms were analysed by CFUs determination and total biomass quantification. Biofilm matrix was examined in terms of total proteins and carbohydrates. Scanner electron microscopy (SEM) was used to observe the structure of Candida biofilms. Furthermore, RT-qPCR was performed to examine the expression levels of BCR1, FKS1 and OLE1 genes present in biofilm cells grown in the presence of the different glucose concentrations. The results demonstrated that glucose influences biofilm formation ability, with an increase in total biomass and number of CFUs, with an increase in a glucose; however in a strain dependent manner. Moreover, the increment of glucose causes an increase on the content of proteins and polysaccharides on C. parapsilosis biofilm matrix. Moreover, BCR1, FKS1 and OLE1 gene expression increased with the glucose increment. In addition, SEM images revealed the presence of pseudohyphae for higher levels of glucose (2 and 10 %). So, the results suggested that glucose enhanced pseudohyphae formation by the induced expression of OLE1, which influences biofilm structure. The overexpression of BCR1 and FKS1 confirm the influence of glucose in biofilm formation ability and in the carbohydrate synthesis and secretion (present in the matrix), respectively. Summarizing, C. parapsilosis biofilms presented a great capacity to tolerate and grow in the presence of high levels of glucose that seems to be directly implicated in C. parapsilosis virulence.